Sulfur Dioxide Capture by Limestone in a Lab Scale Circulating Fluidized Bed Combustor - Shun, Dowon; Bae, Dal-Hee; Oh, Changsup; Chang Kim, Heon; Kyu Park, Seung (Asian Journal of Chemistry, 2013)
During the combustion of fossil fuel in the industry, SOx and NOx can be emitted. The emission of SOx and NOx gases during the combustion of coal or petroleum pitch in the lab scale circulating fluidized bed has been studied. The emission of SOx can be reduced by limestone in the circulating fluidized bed combustion. N2O emission also reduced after the introduction of limestone pulse in the beginning stage. The emission level at the Herbei coal combustion at 900 ºC after introduction of 50 g of T limestone pulse was rapidly decreased from 1200 ppm to 10 ppm.